2018
DOI: 10.1002/pld3.103
|View full text |Cite
|
Sign up to set email alerts
|

Peptide signaling molecules CLE5 and CLE6 affect Arabidopsis leaf shape downstream of leaf patterning transcription factors and auxin

Abstract: Intercellular signaling mediated by small peptides is critical to coordinate organ formation in animals, but whether extracellular polypeptides play similar roles in plants is unknown. Here we describe a role in Arabidopsis leaf development for two members of the CLAVATA 3/ ESR ‐ RELATED peptide family, CLE 5 and CLE 6, which lie adjacent to each other on chromosome 2. Uniquely among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…We generated an hct null mutant by CRISPR/Cas9-mediated gene inactivation as described earlier (DiGennaro et al, 2018). Briefly, BbsI restriction enzyme was used to introduce into the At-psgR/GW plasmid a double strand fragment resulting from 5’-GATTGCTCGGTGGCAGGCCGGACCA and 5’-AAACTGGTCCGGCCTGCCACCGAGC oligonucleotides annealing, which targets HCT region CTCGGTGGCAGGCCGGACCATGG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated an hct null mutant by CRISPR/Cas9-mediated gene inactivation as described earlier (DiGennaro et al, 2018). Briefly, BbsI restriction enzyme was used to introduce into the At-psgR/GW plasmid a double strand fragment resulting from 5’-GATTGCTCGGTGGCAGGCCGGACCA and 5’-AAACTGGTCCGGCCTGCCACCGAGC oligonucleotides annealing, which targets HCT region CTCGGTGGCAGGCCGGACCATGG.…”
Section: Methodsmentioning
confidence: 99%
“…DiGennaro et al, 2018). Briefly, BbsI restriction enzyme was used to introduce into the Atwhich targets HCT region CTCGGTGGCAGGCCGGACCATGG.…”
mentioning
confidence: 99%
“…BOP1/2 promote the expression of FIL , which could stimulate the mediolateral expansion of the leaf blade at specific positions along the proximodistal axis [134]. In addition, BOP1/2 promote the expression of two proximally expressed CLE (CLAVATA-LIKE EMBRYO SURROUNDING REGION) peptide-encoding genes that are simultaneously upregulated by WOX1 and repressed by AS2 [137]. CLEs typically have intercellular signaling roles and bind to leucine-rich receptor-like kinases.…”
Section: Control Of Mediolateral Patterning Along the Proximodistamentioning
confidence: 99%
“…Previous studies have indicated that the CLE5 and CLE6 peptides singly and together showed the rosette leaf shape phenotype. These two genes are also expressed at the base above the abscission zone of the flower organ (Jun et al, 2010;DiGennaro et al, 2018). GhCLE28.1 was found to be in the same subfamily as AtCLE5 and AtCLE6.…”
Section: Discussionmentioning
confidence: 99%